An analysis on security awareness of social networks users - Darvishi, Mahdi (2013)
Online social networking develops interactions and communication approaches. Online environment is the most beneficial approach for retention and inception of social relations. However, by developing facilities in online services the threats of privet security is increase. The information security vulnerability is an emerging problem in the online social networks social networks. The more users join, the more active they are, the more possible risk of personal information disclosure due to lack of self and social awareness on user behavior in the social networks. The main objective of the study is to investigate the components affecting information security behavior in enhancing awareness and design an information security behavior model in enhancing awareness. The quantitative research has been conducted on students studying at University Technology Malaysia. The study has found significant relationship between self-efficacy, security practice- care behavior, intention to practice privacy protection on information security awareness behavior. At the end, recommendations for future studies and limitations of the study were further established.